Strategies for fostering inclusive classrooms in higher education : international perspectives on equity and inclusion - Hoffman, Jaimie; Blessinger, Patrick; Makhanya, Mandla (Innovations in higher education teaching and learning, 2019)
Higher education institutions continue to address an increasingly complex set of issues regarding equity, diversity and inclusion. Many institutions face mounting pressure to find innovative solutions to eliminate access, participation, and achievement barriers as well as practices that impede retention and graduation rates in higher education. This volume provides educators with a global understanding of the challenges associated with the growing diversity of student identities in higher education and provides evidence-based strategies for addressing the challenges associated with implementing equity and inclusion at different higher education institutions around the world.